2016
DOI: 10.1016/j.gie.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiopancreatoscopy

Abstract: This document was reviewed and approved by the Governing Board of the American Society for Gastrointestinal Endoscopy. TECHNICAL CONSIDERATIONS Cholangioscopy usually is performed via the per-oral route, although percutaneous and surgically created routes also are feasible. Different cholangioscopy platforms accommodate these varied approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 127 publications
0
48
0
5
Order By: Relevance
“…The specific role for MAIT cells in the pathogenesis of PSC is currently unclear. However, the possibility to assess bile duct MAIT cells together with recent technological development within cholangioscopic methods will allow for future studies dissecting this in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…The specific role for MAIT cells in the pathogenesis of PSC is currently unclear. However, the possibility to assess bile duct MAIT cells together with recent technological development within cholangioscopic methods will allow for future studies dissecting this in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…The currently available instruments for endoscope-based cholangiopancreatoscopy in the United States are the following [6]:…”
Section: Endoscope-based Systemsmentioning
confidence: 99%
“…operators in a large number of cases [6,[9][10][11]. These limitations along with improved new systems have gradually eliminated the need for endoscope-based systems.…”
Section: Endoscope-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stone fragmentation can be performed under direct vision using either electrohydraulic lithotripsy (EHL) or laser lithotripsy (LL) probes passed down the therapeutic channel. Published series suggest stone clearance using EHL in 74%–95% of patients 17. Early experience from the UK has shown that in patients in whom conventional ERCP was unsuccessful, Spyglass DS and EHL led to complete stone clearance in 81% of cases 18.…”
Section: Recent Advancesmentioning
confidence: 99%